Development of a Methodology of the Product Line Matrix Formation of the Enterprise Fabricating Clothes - Violetta K. Shkuropatskaya; Inna L. Klochko; Lyudmila Y. Falko (International Review of Management and Marketing, 2016)
The paper has considered the questions connected with formation of the rational range of the enterprises for production of clothes. It has also analysed the factors influencing the range formation subject to the principles of the rational wardrobe design (a capsular approach and a colour type of a man's appearance). The paper has developed the algorithm of the range formation of the enterprises fabricating clothes in a mass-market segment on the basis of a brand standard subject to the principle of rational wardrobe. It has created the mathematical model of a rational a product line matrix of the sewing enterprise in a mass-market segment.